An Analysis of the Students’ Competence in Writing Abstract - Sudiran - Sudiran; AB Prabowo Kusumo Adi (ETERNAL (English Teaching Journal), 2023)
Abstract. Writing plays an essential role in the development of students’ ability to disseminate their ideas or research findings. In university, Students need to write research reports as one of the requirements to achieve scholar degree. It means that writing enables students to write academic papers from which they report their findings to the examiners board. Students are expected to know some techniques of writing that help them write a good research report. One of the important elements of writing research is an abstract that enables students to describe the whole content of the research in brief. Therefore, it is necessary to investigate students’ competence in writing a good abstract because not only does it function as a summary of research consisting of introduction, method, finding, and conclusion, but it also functions as a key to arouse the readers’ attention.  The objective of the research is to describe the students’ competence in writing an intelligible research abstract. Data was collected through the 27 students’ abstracts of the research report at the English Language Education Department of the Universitas Muhammadiyah Malang. The results of the research indicate that the student’s competence in writing a research abstract was good. The students’ competence in writing their ideas in an abstract was good, and their ability to write a good topic sentence was good. The findings were strengthened by the computation of five aspects of writing proficiency that showed 25.8 for content value, 16.7 for organization, 16.6 for vocabulary, 17.1 for language use, and 3.8 for mechanics value.